Pengembangan Sistem Informasi Penilaian Hasil Belajar Siswa berbasis Web pada SMA Brawijaya Smart School - Siti Masyruhatin; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
SMA Brawijaya Smart School is an upper secondary school under the auspices of Universitas Brawijaya. Each year, the student of SMA Smart Brawijaya High School reaches an average of 450 people and the teacher reaches 34 people. With such a large number of students and teacher, SMA Brawijaya Smart School still uses Microsoft Excel in assessing student learning outcomes. The administration section must convert one file individually created by the educator into a leger before being converted into a report card format. Another problem that is about the conversion process that is not going well because the teacher makes a mistake that makes the Microsoft Excel file format that has been set up a part of the administration to be changed. The administrative part must be returned back one by one file that was transferred so the conversion process changes. Based on the published problems, a computerized information system was developed using the waterfall method and the Unified Modeling Language (UML) to install the report-making process in the SMA Brawijaya Smart School. Analysis of needs resulted in 43 functional needs and 2 functional needs. System testing is using black-box testing, compatibility testing and User Acceptance Testing (UAT). The result of black-box is 70 test cases with 100% valid results. And compatibility testing result is causing minor and major problems in some browsers that have some incompatible CSS properties. In testing User Acceptance Testing (UAT) has a yield of 82%, which means the student learning outcomes information system is very accepted by the user.